Pengaruh Sponsor-Program Congruence dan Product Placement terhadap Brand Awareness dan Purchase Intention: Analisis Empiris dalam Konteks Sponsorship Drama Korea - Youana Agustina Lopies; Basrah Saidani; Agung Kresnamurti Rivai P (Fakultas Ekonomi Universitas Negeri Jakarta, 2021)
This study aims to determine the effect of sponsor-program congruence and product placement on brand awareness and purchase intention of Samsung smartphones in Indonesia in the context of Korean drama sponsorship. The data collection method used a survey with an instrument in the form of a questionnaire distributed online for approximately 30 days. The sampling technique uses non-probability sampling with a sample size of 200 respondents domiciled in Indonesia and more or equal to 17 years old who have watched Korean dramas sponsored by Samsung and/or there is a Samsung smartphone placement. Data were analyzed using PLS-SEM and assisted by SmartPLS 3.2.9 software. Results showed that there are 5 out of 7 hypotheses were supported. Those hypotheses are: (1) the sponsor-program congruence variable has a positive and significant effect on brand awareness, (2) the product placement variable has a positive and significant effect on brand awareness, (3) brand awareness has a positive and significant effect on purchase intention, (4) the sponsor-program congruence variable has a positive and significant effect on purchase intention mediated by brand awareness, and (5) the product placement variable has a positive and significant effect on purchase intention mediated by brand awareness.